2015
DOI: 10.7883/yoken.jjid.2014.385
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infections in Pediatric Intensive Care Units in Turkey: a National Point-Prevalence Survey

Abstract: SUMMARY: Health care-associated infections (HCAIs) cause considerable morbidity and mortality in pediatric intensive care units (PICUs). The objective of this point prevalence study was to assess the burden of HCAIs in PICUs in Turkey. Fifty PICUs participated in this study. Data regarding demographics, microbiological findings, therapeutic interventions, and outcomes were collected for all PICU inpatients. A total of 327 patients participated in the study: 122 (37z) experienced 1 or more HCAI. The most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
1
9
1
1
Order By: Relevance
“…In the present study, it was believed that the low level rates detected in urinary tract infections was the result of the practice that urine cannula placing times are kept short, taking them of as soon as the urinary catheterization requirement finishes. In studies conducted in pediatric intensive care units, ventilator-associated pneumonia rate varied between 5-13.1%, whereas in our study the number of patients with ventilator-associated pneumonia was 30 (1.18%) (21).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In the present study, it was believed that the low level rates detected in urinary tract infections was the result of the practice that urine cannula placing times are kept short, taking them of as soon as the urinary catheterization requirement finishes. In studies conducted in pediatric intensive care units, ventilator-associated pneumonia rate varied between 5-13.1%, whereas in our study the number of patients with ventilator-associated pneumonia was 30 (1.18%) (21).…”
Section: Discussioncontrasting
confidence: 72%
“…Bloodstream infections are one of the main subtypes of healthcare-associated infections both worldwide and in Turkey (7,16). In a multi-centered point prevalence study conducted in Turkey, in 322 cases, laboratory proven bloodstream infection was detected in 24 (7.3%) (21).…”
Section: Discussionmentioning
confidence: 99%
“…The carbapenem resistance rates have been reported to be between 29 and 37% in those studies. [1][2][3] Another study conducted in our hospital between 2011 and 2013 had revealed a higher rate of resistance to meropenem by Pseudomonas spp. which was 54%.…”
Section: Discussionmentioning
confidence: 88%
“…They prolong hospital stay, increase antibiotic usage and the development of resistance to antibiotics, and cause increased health care expenses. [1][2][3] NIs are more common in intensive care units (ICUs) than other units and patients hospitalized in ICUs experience multidrugresistant infections much more than others due to longer hospitalization, frequent exposure to invasive procedures, and manipulations. 3 The pathogens causing NIs in ICUs are mostly opportunistic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Kan akımı enfeksiyonları hem ülkemiz hem de dünyada HE'lerin başlıca alt tiplerinden biridir (7,16). Ülkemizde yapılan çok merkezli bir nokta prevalans çalışmasında laboratuvar ile kanıtlanmış kan akımı enfeksiyonu 322 olgunun 24 (%7.3)'ünde saptanmıştı (21). Avrupa menşeili çok uluslu bir çalışmada yoğun bakım ünitelerine 6 ayda yatırılan 710 olgudan 13 (%1.9)'ünde santral kateter ilişkisiz, 21 (%2.9)'inde kateter ilişkili kan akımı enfeksiyonu saptandığı bildirilmiştir.…”
Section: Bulgularunclassified